Defining clinically important perioperative blood loss and transfusion for the Standardised Endpoints for Perioperative Medicine (StEP) collaborative: a protocol for a scoping review. Issue 6 (30th June 2017) - Bartoszko, Justyna; Vorobeichik, Leon; Jayarajah, Mohandas; Karkouti, Keyvan; Klein, Andrew A; Lamy, Andre; Mazer, C David; Murphy, Mike; Richards, Toby; Englesakis, Marina; Myles, Paul S; Wijeysundera, Duminda N
Abstract : Introduction: 'Standardised Endpoints for Perioperative Medicine' (StEP) is an international collaboration undertaking development of consensus-based consistent definitions for endpoints in perioperative clinical trials. Inconsistency in endpoint definitions can make interpretation of trial results more difficult, especially if conflicting evidence is present. Furthermore, this inconsistency impedes evidence synthesis and meta-analyses. The goals of StEP are to harmonise definitions for clinically meaningful endpoints and specify standards for endpoint reporting in clinical trials. To help inform this endeavour, we aim to conduct a scoping review to systematically characterise the definitions of clinically important endpoints in the existing published literature on perioperative blood loss and transfusion. Methods and analysis: The scoping review will be conducted using the widely adopted framework developed by Arksey and O'Malley, with modifications from Levac. We refined our methods with guidance from research librarians as well as researchers and clinicians with content expertise. The electronic literature search will involve several databases including Medline, PubMed-not-Medline and Embase. Our review has three objectives, namely to (1) identify definitions of significant blood loss and transfusion used in previously published large perioperative randomised trials; (2) identify previously developed consensus-based definitions for significant blood loss and transfusion in perioperative medicine and related fields; and (3) describe the association between different magnitudes of blood loss and transfusion with postoperative outcomes. The multistage review process for each question will involve two reviewers screening abstracts, reading full-text articles and performing data extraction. The abstracted data will be organised and subsequently analysed in an iterative process. Ethics and dissemination: This scoping review of the previously published literature does not require research ethics approval. The results will be used to inform a consensus-based process to develop definitions of clinically important perioperative blood loss and transfusion. The results of the scoping review will be published in a peer-reviewed scientific journal.